Design of Mobile Finger Communications Board for Stroke Patient Using The Five Planes of User Experience - Priana, Aan Jelli; Tolle, Herman; Aknuranda, Ismiarta; Arisetijono, Eko (Journal of Information Technology and Computer Science, 2017)
Stroke, in 2014 to mid-2015 is the first cause of death in Indonesia. The condition of stroke patients whose movements are limited is exacerbated by the psychic condition of patients who are unable to communicate pressure will cause obstacles to the healing process of the patient. This research is designed based on the five planes of user experience which are divided into five areas: strategy, scope, structure, skeleton, and surface. This communication board is operated using the patient's fingers so that it is comfortable for everyday activities. The result of Mobile Finger Communication Board implementation shows that application usability level seen from perception and ergonomic point of view shows satisfaction index of the user at the satisfactory level so that it can be said that the system works with the satisfactory result of the users. It is expected that with the Mobile Finger Communication Board which will be used daily to support the healing process of stroke so that the healing rate of stroke is increasing.